Studi Difusi Ca2+ Pada Sinapsis Menggunakan Metode Monte Carlo Cell: Ester Ratna Sari, Giner Maslebu, Adita Sutresno - Ester Ratna Sari Ester Ratna Sari; Giner Maslebu Giner Maslebu; Adita Sutresno Adita Sutresno (Jurnal Fisika dan Aplikasinya, 2020)
Diffusion process became one of the important mechanisms in the human body system, such as in the nervous system which is the Ca2+diffusion in the synapses. This research aims to study the Ca2+diffusion process if Gd inhibits Ca2+channel in pre-synapses. This study did not use Gd, but it was modeled with various numbers of Ca2+ channels. The less number of Ca2+opened channels described the more Gd which inhibited Ca2+ channels. The Monte Carlo Cell Method (MCell) was used in this study. The synapses model was made using Blender 2.76b; consisted of two compartments illustrated with two circles. The molecule in the outside pre-synapses compartment interacted with the molecular surface of the pre-synapses compartment and resulted in a molecule in pre-synapses. The result of the simulation process for the molecules reached half of the variations in the number of total area channels. The time needed being 0.65s, 0.34s, 0.24s, and 0.18s, from the smallest to the biggest respectively. The times needed for density variations from big to small were 0.337s, 0.362s, and 0.364s respectively. The number of the diffused molecules in the backward rate variation within the same time was 3928, 3626, 2037, and 529 molecules respectively.